2012
DOI: 10.1136/injuryprev-2012-040548
|View full text |Cite
|
Sign up to set email alerts
|

More fatal all-terrain vehicle crashes occur on the roadway than off: increased risk-taking characterises roadway fatalities

Abstract: BackgroundAll-terrain vehicles (ATVs) have steadily increased in popularity, size and speed, characteristics that likely contribute to the alarming rise in ATV-related fatalities. One potentially high-risk activity is riding on the road.ObjectivesTo compare fatal ATV crashes that occur on the roadway and off, to more fully understand factors that contribute to fatalities at each location.MethodsFatality data from the US Consumer Product Safety Commission (CPSC) were used for descriptive and comparative analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
86
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(94 citation statements)
references
References 28 publications
8
86
0
Order By: Relevance
“…We hypothesized that this proportion did not fully reveal the problem of passengers on ATVs, as it failed to take into account injured operators who may have been at increased risk of a crash due to the presence of additional riders. Consistent with this hypothesis, we found that from 1985-2009, 29% of all U.S. ATV-related fatalities were operators with passengers or passengers themselves [8].…”
Section: Introductionsupporting
confidence: 75%
See 3 more Smart Citations
“…We hypothesized that this proportion did not fully reveal the problem of passengers on ATVs, as it failed to take into account injured operators who may have been at increased risk of a crash due to the presence of additional riders. Consistent with this hypothesis, we found that from 1985-2009, 29% of all U.S. ATV-related fatalities were operators with passengers or passengers themselves [8].…”
Section: Introductionsupporting
confidence: 75%
“…In previous studies, passengers represented approximately 15% of crash victims [8,9,18,19], and 9% of all U.S. ATV-related hospitalizations [20]. We hypothesized that this proportion did not fully reveal the problem of passengers on ATVs, as it failed to take into account injured operators who may have been at increased risk of a crash due to the presence of additional riders.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Small numbers of child fatalities have been reported in contexts other than on public highways, including low-speed vehicle run-over fatalities in young children 43 and all-terrain vehicles driven by young people. 44 While much progress has been made in reducing transport fatalities, this remains one of the areas most amenable to further prevention through legislation, environmental modification, engineering, education and training. 45,46 …”
Section: Traffic Deathsmentioning
confidence: 99%